Evi9 Encodes a Novel Zinc Finger Protein That Physically Interacts with BCL6, a Known Human B-Cell Proto-Oncogene Product - Nakamura, Takuro (American Society for Microbiology, 2000)
Evi9 is a common site of retroviral integration in BXH2 murine myeloid leukemias. Here we show that Evi9 encodes a novel zinc finger protein with three tissue-specific isoforms: Evi9a (773 amino acids [aa]) contains two C(2)H(2)-type zinc finger motifs, a proline-rich region, and an acidic domain; Evi9b (486 aa) lacks the first zinc finger motif and part of the proline-rich region; Evi9c (239 aa) lacks all but the first zinc finger motif. Proviral integration sites are located in the first intron of the gene and lead to increased gene expression. Evi9a and Evi9c, but not Evi9b, show transforming activity for NIH 3T3 cells, suggesting that Evi9 is a dominantly acting proto-oncogene. Immunolocalization studies show that Evi9c is restricted to the cytoplasm whereas Evi9a and Evi9b are located in the nucleus, where they form a speckled localization pattern identical to that observed for BCL6, a human B-cell proto-oncogene product. Coimmunoprecipitation and glutathione S-transferase pull-down experiments show that Evi9a and Evi9b, but not Evi9c, physically interact with BCL6, while deletion mutagenesis localized the interaction domains in or near the second zinc finger and POZ domains of Evi9 and BCL6, respectively. These results suggest that Evi9 is a leukemia disease gene that functions, in part, through its interaction with BCL6.